Fabrication, Investigation, and Application of Light-Responsive Self-Assembled Nanoparticles - Pang, Juan; Gao, Ziyu; Tan, Huaping; Mao, Xincheng; Xu, Jialing; Kong, Jingyang; Hu, Xiaohong (Frontiers in Chemistry, 2019)
Light-responsive materials attract increasing interest in recent years on account of their adjustable on-off properties upon specific light. In consideration of reversible isomerization transition for azobenzene (AZO), it was designed as light-responsive domain for nanoparticles in this research. At the same time, the interaction between AZO domain and β-cyclodextrin (β-CD) domain was designed as a driving force to assemble nanoparticles, which was fabricated by two polymers containing AZO domain and β-CD domain, respectively. The formed nanoparticles were confirmed by Dynamic Light Scattering (DLS) results and Transmission Electron Microscope (TEM) images. Obvious two-phase structure was formed in which the outer layer of nanoparticles was composed of PCD polymer, as verified by 1H NMR spectroscopy. The efficient and effective light response of the nanoparticles including quick responsive time, controllable and gradual recovered process, good fatigue resistance was confirmed by UV-Vis spectroscopy. The size of nanoaprticle could be adjusted by polymer ratio and light irradiation, which was ascribed to its light-response property. Nanoparticles had irreversibly pH dependent characteristic. In order to explore its application as a nanocarrier, drug loading and in vitro release profile in different environment was investigated through control of stimuli including light or pH value. Folic acid (FA), as a kind of target fluorescent molecule with specific protein-binding property, was functionalized onto nanoparticles for precise delivery for anticancer drug. Preliminary in vitro cell culture results confirmed efficient and effective curative effect for the nanocarrier on MCF-7 cells.